Electric resistance welded steel pipe and method for manufacturing same

By controlling the shear residual stress and steel structure on the steel pipe surface during the manufacturing process of online pipe steel pipes, the problem of difficult high-strength steel pipes in the prior art to take into account both SSC resistance, and a resistance welded steel pipe with high strength and excellent SSC resistance is achieved.

CN119744313APending Publication Date: 2025-04-01JFE STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060814.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-05-22
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to improve the sulfide stress corrosion cracking (SSC) resistance of steel pipes for wire pipes while ensuring high strength, especially when the hardness of the inner surface of the steel pipe is excessively increased.

Method used

By appropriately controlling the shear residual stress on the surface of the steel pipe, its absolute value is reduced to improve the SSC resistance of the steel pipe. The specific method includes controlling the circumference and shear residual stress of the inner surface of the resistance-welded steel pipe during the manufacturing process, ensuring that it is above 10MPa but below 300MPa, and optimizing the volume ratio and crystal particle size of ferrite and bainite in the steel structure.

Benefits of technology

The SSC resistance of resistance-welded steel pipes is achieved at a high strength while significantly improving, ensuring that no cracking occurs in the 4-point bending corrosion test, and controlling the depth and depth/width ratio of the hole corrosion are within the appropriate range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005277688890000171
    Figure BDA0005277688890000171
  • Figure BDA0005277688890000181
    Figure BDA0005277688890000181
  • Figure BDA0005277688890000221
    Figure BDA0005277688890000221
Patent Text Reader

Abstract

Provided is a high-strength electric resistance welded steel pipe having excellent SSC resistance. Wherein the absolute value of the residual stress in the circumferential direction of the inner surface of the electric-resistance-welded steel pipe is 10 MPa or more, the absolute value of the shear residual stress in the inner surface is 300 MPa or less, the total volume fraction of ferrite and bainite in the steel structure in the center of the thickness of the base material part of the electric-resistance-welded steel pipe is 90% or more, and the average crystal grain size is 9.0 [mu] m or less. And the total volume fraction of ferrite and bainite in the steel structure at a position 0.1 mm outward in the radial direction of the tube from the inner surface of the base material part is 95% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-strength electric-resistance-welded steel pipe preferably used for a wire pipe or the like and a method for manufacturing the same. Background Art

[0002] Steel pipes for line pipes used for long-distance transportation of crude oil, natural gas, etc. improve transportation efficiency by increasing the pressure of the internal fluid, so high strength is required.

[0003] In addition, since the inner surface of a line pipe steel pipe is in contact with a highly corrosive fluid containing hydrogen sulfide, high resistance to sulfide stress corrosion cracking (SSC) is also required.

[0004] Generally, if the strength of a steel material increases, the SSC resistance of the steel material decreases. In particular, in order to ensure the SSC resistance of a steel pipe for a line pipe, it is important to reduce the hardness (strength) of the inner surface of the steel pipe in contact with the fluid.

[0005] Generally, the TMCP (Thermo-Mechanical Control Process) technology combining controlled rolling and accelerated cooling is applied in the production of raw plates of high-strength steel pipes. The steel structure is refined by using the TMCP technology, thereby increasing the strength of the steel material.

[0006] In the TMCP technology, it is important to increase the cooling rate during accelerated cooling, but the cooling rate of the steel plate surface is higher than that of the steel plate interior. Therefore, the hardness of the steel plate surface becomes excessively high. As a result, from the viewpoint of SSC resistance, it is difficult to apply the steel plate manufactured by the TMCP technology to wire pipes.

[0007] In order to cope with the above-mentioned problems, for example, Patent Documents 1 or 2 propose steel pipes with controlled surface hardness.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 6521197

[0011] Patent Document 2: Japanese Patent Application Publication No. 2017-179482 Summary of the invention

[0012] However, as described in Patent Documents 1 and 2, even if the surface hardness of a steel pipe is controlled, sufficient SSC resistance may not be obtained, and further improvement of SSC resistance is required.

[0013] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a high-strength electric-resistance-welded steel pipe having excellent SSC resistance and a method for producing the same.

[0014] It should be noted that the term "high strength" as used in the present invention means that the yield strength of the base material portion of the electric resistance welded steel pipe is 400 MPa or more in a tensile test described later.

[0015] The term "excellent SSC resistance" as used herein means that in the 4-point bending corrosion test described below, the base material portion of the electric resistance welded steel pipe does not crack, the depth of the generated pitting is less than 250 μm, and the maximum value of the pitting (depth / width) is less than 3.0.

[0016] Each of the above tests can be performed by the methods described in the examples described later.

[0017] The present inventors have conducted intensive studies to achieve the above-mentioned object and have found that SSC resistance can be improved by appropriately controlling the shear residual stress on the surface of a steel pipe.

[0018] In the present invention, “the shear residual stress is high” means “the absolute value of the shear residual stress is large”. Also, “the shear residual stress is low” means “the absolute value of the shear residual stress is small”.

[0019] Since the proliferation of dislocations in the crystals in the steel pipe is caused by shear stress, if the shear residual stress is high, the proliferation of dislocations is promoted when the stress is applied. Therefore, the line pipe using a steel pipe with high shear residual stress on the surface has an increased dislocation density near the surface due to the pressure during operation. As a result, the hardness of the steel pipe surface increases and the SSC resistance decreases.

[0020] Therefore, it can be seen that the SSC resistance of the steel pipe can be improved by reducing the shear residual stress on the surface of the steel pipe.

[0021] The present invention has been completed based on the above findings.

[0022] That is, the gist of the present invention is as follows.

[0023] 1. A resistance welded steel pipe having a base material portion and a resistance welded portion,

[0024] The absolute value of the residual stress in the circumferential direction of the inner surface of the electric resistance welded steel pipe is 10 MPa or more.

[0025] The absolute value of the shear residual stress on the inner surface of the tube is less than 300 MPa,

[0026] In the steel structure at the center of the wall thickness of the base material portion, the combined volume fraction of ferrite and bainite is 90% or more, and the average grain size at the center of the wall thickness is 9.0 μm or less.

[0027] In the steel structure at a position 0.1 mm outside in the radial direction of the tube from the inner surface of the base material portion, the total volume fraction of ferrite and bainite is 95% or more.

[0028] 2. The electric resistance welded steel pipe according to item 1 above, characterized in that:

[0029] The component composition of the base material portion includes, by mass %,

[0030] C: 0.020%~0.150%,

[0031] Si: 0.01% to 0.50%,

[0032] Mn: 0.30% to 2.00%,

[0033] P: 0.050% or less,

[0034] S: 0.0200% or less,

[0035] Al: 0.005% to 0.100%,

[0036] N: 0.0100% or less,

[0037] The remainder is Fe and inevitable impurities.

[0038] 3. The electric resistance welded steel pipe according to 2 above, characterized in that:

[0039] The above composition also includes, by mass%,

[0040] Nb: 0.100% or less,

[0041] V: 0.100% or less,

[0042] Ti: 0.150% or less,

[0043] Cr: 1.00% or less,

[0044] Mo: 1.00% or less,

[0045] Cu: 1.00% or less,

[0046] Ni: 1.00% or less,

[0047] Ca: 0.0100% or less,

[0048] B: 0.0100% or less

[0049] 1 or more of the following.

[0050] 4. A method for manufacturing an electric resistance welded steel pipe, which is the method for manufacturing an electric resistance welded steel pipe according to any one of 1 to 3 above, comprising: a hot rolling step, in which the steel billet is heated to a heating temperature of 1100°C to 1300°C, and then hot rolled at a finishing temperature of 750°C to 850°C; a cooling step, in which, after the hot rolling step, an average cooling rate at the center of the plate thickness is 10°C / s to 60°C / s, a cooling stop temperature at the center of the plate thickness is 450°C to 650°C, and a cooling stop temperature at the plate surface is 25 The invention relates to a method for manufacturing a steel pipe having a heat treatment process, wherein the steel pipe is cooled from 0°C to 500°C to form a hot-rolled steel plate; a pipe making process, after the cooling process, the hot-rolled steel plate is formed into a cylindrical shape by cold rolling roll forming, and the circumferential ends of the cylindrical shape are butted and then resistance welded; a sizing process, after the pipe making process, the steel pipe is passed through a sizing roll satisfying the following formula (1) to form a resistance welded steel pipe billet; and an internal pressure loading process, after the sizing process, an internal pressure p (MPa) satisfying the following formula (2) is loaded on the inner surface of the resistance welded steel pipe billet to form a resistance welded steel pipe.

[0051] Diameter of sizing roller (mm) ≥ thickness of hot-rolled steel plate (mm) / 0.020···(1)

[0052] X<p≤X×1.5···(2)

[0053] It should be noted that X = (wall thickness of electric resistance welded steel tube billet (mm) / radius of electric resistance welded steel tube billet (mm)) × yield strength of electric resistance welded steel tube billet (MPa)

[0054] According to the present invention, a high-strength electric-resistance welded steel pipe having excellent SSC resistance and an advantageous method for producing the high-strength electric-resistance welded steel pipe can be provided. DETAILED DESCRIPTION

[0055] The high-strength electric resistance welded steel pipe according to the present invention is an electric resistance welded steel pipe having a base material portion and an electric resistance welded portion. In the steel structure at the center of the wall thickness of the base material portion, the combined volume fraction of ferrite and bainite is 90% or more, and the average grain size at the center of the wall thickness is 9.0 μm or less. In addition, in the steel structure at a position 0.1 mm outside the tube in the radial direction from the tube inner surface of the base material portion, the combined volume fraction of ferrite and bainite is 95% or more. Furthermore, the absolute value of the circumferential residual stress on the tube inner surface of the electric resistance welded steel pipe is 10 MPa or more, and the absolute value of the shear residual stress on the tube inner surface is 300 MPa or less.

[0056] The following is an explanation of the electric resistance welded steel pipe and its manufacturing method of the present invention. It should be noted that the present invention is not limited to the following embodiments. In addition, the present invention stipulates the component composition and steel structure of any position of the base material part other than the electric resistance welded part and the heat affected part of the electric resistance welded steel pipe. That is, whether it is a position 90° away from the electric resistance welded part or a position 180° away from the electric resistance welded part, the component composition and steel structure are the same.

[0057] It should be noted that in the following description, the high-strength electric-resistance-welded steel pipe may be simply referred to as a "electric-resistance-welded steel pipe".

[0058] Ferrite and bainite are soft structures, while pearlite, martensite, and austenite are hard structures that are easily formed as the cooling rate after hot rolling increases.

[0059] The total volume ratio of ferrite and bainite in the center of the wall thickness of the base material: 90% or more

[0060] If the combined volume fraction of ferrite and bainite at the center of the wall thickness of the base material portion (meaning the 1 / 2 position of the thickness of the base material portion of the steel pipe, hereinafter referred to as the "center of the wall thickness") is less than 90%, the volume fraction of the hard structure in the pipe surface layer becomes high, and the SSC resistance decreases.

[0061] Here, regarding the cooling rate of the steel plate after hot rolling, since the steel plate surface is relatively higher than the steel plate interior, the ratio of the hard structure on the steel plate surface becomes higher than that on the steel plate interior. Therefore, since the hot-rolled steel plate having the above structure is used as an electric resistance welded steel pipe, the ratio of the hard structure on the side closer to the pipe surface in the electric resistance welded steel pipe becomes higher than that on the center of the wall thickness.

[0062] In addition, the combined volume fraction of ferrite and bainite in the center of the wall thickness is preferably 93% or more. The volume fraction is more preferably 96% or more. It should be noted that the upper limit of the volume fraction is not particularly limited. From the viewpoint of SSC resistance, the volume fraction is preferably as high as possible, but since it is difficult to completely suppress the formation of the remaining part of the structure, the volume fraction may be 99% or less.

[0063] The remaining part in the center of the wall thickness is one or more of pearlite, martensite and austenite. If the total volume fraction of these structures exceeds 10%, the volume fraction of the hard structure near the tube surface becomes high, and the SSC resistance decreases. Therefore, the total volume fraction of these structures is 10% or less relative to the entire steel structure at the same position. The volume fraction is preferably 7% or less, and more preferably 4% or less.

[0064] Average grain size at the center of the wall thickness: 9.0 μm or less

[0065] The smaller the average crystal grain size, the higher the yield stress. In the present invention, in order to ensure the desired strength, the average crystal grain size at the center of the wall thickness is 9.0 μm or less. The average crystal grain size is preferably 8.5 μm or less, and more preferably 8.0 μm or less.

[0066] It should be noted that the lower limit of the average crystal grain size is not particularly limited, but if the average crystal grain size is reduced, the dislocation density increases and the SSC resistance decreases, so it is preferably 3.0 μm or more.

[0067] The total volume ratio of ferrite and bainite at a position 0.1 mm outside the tube in the radial direction from the inner surface of the base material: 95% or more

[0068] If a hard structure is mixed with ferrite and bainite, shear residual stress is generated at the interface due to stress concentration caused by the hardness difference. Therefore, if the combined volume fraction of ferrite and bainite near the inner surface of the tube is low and the volume fraction of the hard structure becomes high, the SSC resistance is reduced. Therefore, the combined volume fraction of ferrite and bainite at the 0.1mm position (hereinafter also referred to as the "0.1mm position") on the outside of the tube in the radial direction from the inner surface of the tube of the parent material part (hereinafter referred to as the "inner surface of the tube") is 95% or more relative to the overall steel structure at the same position. The volume fraction is preferably 96% or more, and more preferably 97% or more. It should be noted that the upper limit of the volume fraction is not particularly limited. From the viewpoint of SSC resistance, it is preferred that the volume fraction is as high as possible, but since it is difficult to completely suppress the generation of the remaining part of the structure, the volume fraction can be 99% or less.

[0069] The remaining portion at the 0.1 mm position is one or more of pearlite, martensite and austenite. If the total volume fraction of these organizations exceeds 5%, the SSC resistance decreases. Therefore, the total volume fraction of these organizations is 5% or less relative to the entire steel organization at the same position. The volume fraction is preferably 4% or less, and more preferably 3% or less.

[0070] In the present invention, within the range from 1 / 2 of the thickness of the base material portion of the steel pipe to ±1.0 mm in the wall thickness direction (depth direction), the thickness of the steel pipe is within 0.10 mm. 2 The presence of the steel structure in the center of the wall thickness in an area of ​​about 1.0 mm is a necessary condition for obtaining the above effect. In the present invention, the "steel structure in the center of the wall thickness" means the above 0.10 mm steel structure at any point in the range of ±1.0 mm in the wall thickness direction with the center of the wall thickness as the center. 2 Steel structure within the area of ​​about 100 mm.

[0071] In addition, within the range of ±0.06 mm in the wall thickness direction with the 0.1 mm position as the center, within the range of 0.10 mm 2The presence of the steel structure at the 0.1 mm position is a necessary condition for obtaining the above effect. In the present invention, the "steel structure at the 0.1 mm position" means the above 0.10 mm structure at any point within the range of ±0.06 mm in the wall thickness direction with the 0.1 mm position as the center. 2 Steel structure within the area of ​​about 100 mm.

[0072] Absolute value of residual stress in the circumferential direction of the inner surface of the pipe: 10MPa or more

[0073] If the absolute value of the residual stress in the circumferential direction of the inner surface of the tube is less than 10 MPa, the amount of tube expansion in the internal pressure loading step is too large, so the dislocation density on the tube surface increases and the SSC resistance decreases.

[0074] The reason why the residual stress in the circumferential direction is defined as an absolute value is that the absolute value of the residual stress in the circumferential direction decreases as the amount of pipe expansion in the internal pressure loading step increases.

[0075] The upper limit of the absolute value of the residual stress in the circumferential direction is not particularly limited, but is preferably within a range of 800 MPa or less because the absolute value of the shear residual stress after the internal pressure loading step may become too large.

[0076] Absolute value of shear residual stress on the inner surface of the pipe: 300MPa or less

[0077] If the absolute value of the shear residual stress on the inner surface of the tube exceeds 300 MPa, the proliferation of dislocations in the crystal structure of the steel tube is promoted when stress is applied, and the dislocation density increases, thereby reducing the SSC resistance. The absolute value of the shear residual stress on the inner surface of the tube is preferably 280 MPa or less, and more preferably 260 MPa or less.

[0078] The reason why the shear residual stress is defined as an absolute value is that tensile deformation or compressive deformation is applied from various directions in the use environment, such as tension or compression in the tube axial direction due to bending of the tube and tension in the tube circumferential direction due to internal pressure.

[0079] The lower limit of the absolute value of the shear residual stress on the inner surface of the tube is not particularly limited, but is preferably within a range of 10 MPa or more because it is difficult to make the residual stress in the tube axial direction and the residual stress in the tube circumferential direction both zero.

[0080] Here, the steel structure can be observed by the following method.

[0081] First, a test piece for tissue observation was collected so that the observation surface became a cross section parallel to both the tube axis direction and the wall thickness direction, and after grinding, it was etched with nitric acid alcohol solution (nital). For tissue observation, an optical microscope (magnification: 1000 times) or a scanning electron microscope (SEM, magnification: 1000 times) was used to observe and photograph the structure at the center of the wall thickness and at a position 0.1 mm outside the tube in the radial direction from the inner surface of the tube.

[0082] Next, the area ratios of ferrite, bainite, and the remainder (pearlite, martensite, austenite) were determined from the obtained optical microscope image and SEM image. The area ratio of each structure was observed in 5 viewing fields and calculated as the average value of the values ​​obtained in each viewing field. It should be noted that in the present invention, the area ratio obtained by observing the structure is used as the volume ratio of each structure.

[0083] Ferrite is a product of diffusion phase transformation, with low dislocation density and a basically restored structure. It includes polygonal ferrite and quasi-polygonal ferrite.

[0084] Bainite is a duplex structure of lath-shaped ferrite and cementite with high dislocation density.

[0085] Pearlite is a eutectic structure of iron and iron-carbon compounds (ferrite + cementite), showing a layered structure in which linear ferrite and cementite are arranged alternately. In addition, it includes degenerate pearlite, which is a structure in which point-like cementite is regularly arranged in ferrite.

[0086] Martensite is a lath-shaped low-temperature phase transformation structure with a very high dislocation density. In SEM images, it shows a bright contrast compared to ferrite and bainite.

[0087] It should be noted that it is difficult to distinguish martensite and austenite in optical microscope images and SEM images. Therefore, the area ratio of the structure observed as martensite or austenite is measured from the obtained SEM image, and the value obtained by subtracting the volume ratio of austenite measured by the method described later from the measured value is used as the volume ratio of martensite.

[0088] Austenite belongs to the fcc phase, and using this fact, the volume fraction of austenite is measured by X-ray diffraction. The test piece for measuring the center of the wall thickness is made by grinding so that the diffraction surface becomes the center of the wall thickness and then chemically polishing to remove the surface processing layer. In addition, the test piece for measuring the 0.1mm position is made by mirror polishing so that the diffraction surface becomes the 0.1mm position outside the tube in the radial direction from the inner surface of the tube and then chemically polishing the polished surface to remove the surface processing layer. The Kα line of Mo is used for measurement, and the integrated intensity of the (200), (220), and (311) planes of fcc iron and the (200) and (211) planes of bcc iron are respectively calculated. The volume fraction of austenite is calculated by calculating the ratio of the standardized integrated intensity of austenite in a manner that the standardized integrated intensity obtained by dividing each value by the theoretical intensity value is proportional to the volume fraction of each phase.

[0089] Regarding the measurement of the average crystal grain size, the cross-section parallel to the tube axis direction and the wall thickness direction was mirror-polished, and the histogram of the crystal grain size distribution in the center of the wall thickness was calculated using the SEM / EBSD method (a graph with the crystal grain size on the horizontal axis and the existence ratio of each crystal grain size on the vertical axis), and the arithmetic mean of the crystal grain size was obtained. The measurement conditions were an acceleration voltage of 15 kV, a measurement area of ​​200 μm × 200 μm, and a measurement step length (measurement resolution) of 0.5 μm. The measurement values ​​of 5 fields of view were obtained and averaged. It should be noted that in the analysis of the crystal grain size, crystals with a grain size of less than 2.0 μm were removed from the analysis object as measurement noise.

[0090] The absolute value of the shear residual stress on the inner surface of the pipe was measured by X-ray diffraction on a surface of the inner surface of the center in the longitudinal direction of the electric resistance welded steel pipe that was electrolytically polished to 100 μm.

[0091] The X-ray source is CrKα line, the tube voltage is 30kV, and the tube current is 1.0mA. The measurement is carried out by the cosα method, and the measured lattice plane is (211). The residual stress in the tube axis direction and the tube circumference direction is measured in the resistance welded part and the inner surface of the tube at each position (12 places) at 30 degrees intervals in the tube circumference based on this. Since the above-mentioned shear residual stress is the residual stress near the surface layer, it can be regarded as a plane stress state. The main stress direction is the tube axis direction and the tube circumference direction. The absolute value of the shear residual stress is calculated as the absolute value of ((residual stress in the tube axis direction (MPa) - residual stress in the tube circumference direction (MPa)) / 2).

[0092] However, the residual stress in the tube axis direction or the tube circumferential direction is a positive value in the case of tension and a negative value in the case of compression. When there is no residual stress in the tube axis direction or the tube circumferential direction, the value is set to 0. The absolute value of the shear residual stress at each position is obtained, and the maximum value thereof is taken as the absolute value of the shear residual stress of the present invention.

[0093] The absolute value of the residual stress in the circumferential direction of the inner surface of the tube may be the absolute value of the residual stress in the circumferential direction of the tube measured in the measurement of the absolute value of the shear residual stress on the inner surface of the tube.

[0094] Next, from the viewpoint of ensuring the above-mentioned characteristics and steel structure, the preferred range of the component composition of the electric resistance welded steel pipe (the base material part) and the hot-rolled steel plate used as the blank thereof and the reasons for the limitation are explained. In this specification, "%" indicating the component composition of steel is mass % unless otherwise specified.

[0095] C: 0.020%~0.150%

[0096] C is an element that increases the strength of steel by solid solution strengthening. In addition, C is an element that contributes to the refinement of the structure by lowering the phase transformation starting temperature. In order to ensure the strength required in the present invention, it is preferred to contain 0.020% or more of C. On the other hand, if the C content is greater than 0.150%, the hardenability becomes high and hard pearlite, martensite, and austenite are excessively generated, so the C content is preferably less than 0.150%. The C content is more preferably more than 0.025%, and more preferably less than 0.140%. In addition, the C content is further preferably more than 0.030%, and further preferably less than 0.130%.

[0097] Si: 0.01% to 0.50%

[0098] Si is an element that increases the strength of steel by solid solution strengthening. In order to obtain the above-mentioned effect, it is preferably contained 0.01% or more of Si. On the other hand, if the Si content is greater than 0.50%, the hardenability becomes high and hard pearlite, martensite, and austenite are excessively generated. In addition, it becomes easy to generate oxides in the resistance welding portion, and the weld characteristics are reduced. Therefore, the Si content is preferably less than 0.50%. The Si content is more preferably more than 0.02%, and more preferably less than 0.45%. In addition, the Si content is further preferably more than 0.03%, and further preferably less than 0.40%.

[0099] Mn: 0.30%~2.00%

[0100] Mn is an element that increases the strength of steel by solid solution strengthening. In addition, Mn is an element that contributes to the refinement of the structure by lowering the phase transformation starting temperature. In order to ensure the strength and steel structure required by the present invention, it is preferably contained more than 0.30% Mn. On the other hand, if the Mn content is greater than 2.00%, the hardenability becomes high and hard pearlite, martensite, and austenite are excessively generated, so the Mn content is preferably less than 2.00%. The Mn content is more preferably more than 0.40%, and more preferably less than 1.90%. In addition, the Mn content is further preferably more than 0.50%, and further preferably less than 1.80%.

[0101] P: 0.050% or less

[0102] Since P segregates at grain boundaries and causes inhomogeneity of the material, it is preferred to reduce the P content as much as possible, and the P content is preferably within the range of 0.050% or less. The P content is more preferably 0.040% or less, and further preferably 0.030% or less. It should be noted that the lower limit of P is not particularly specified (usually greater than 0%), but excessive reduction will lead to an increase in smelting costs, so P is preferably 0.001% or more.

[0103] S: 0.0200% or less

[0104] S usually exists in steel as MnS, but MnS is thinly extended in the hot rolling process, which has an adverse effect on ductility and toughness. Therefore, in the present invention, it is preferred to reduce S as much as possible, and the S content is preferably 0.0200% or less. The S content is more preferably 0.0100% or less, and further preferably 0.0050% or less. It should be noted that the lower limit of S is not particularly specified (usually greater than 0%), but excessive reduction will lead to a rise in smelting costs, so S is preferably 0.0001% or more.

[0105] Al: 0.005% to 0.100%

[0106] Al is an element that acts as a strong deoxidizer. In order to obtain such an effect, it is preferable to contain 0.005% or more of Al. On the other hand, if the Al content exceeds 0.100%, the weldability deteriorates and the number of alumina inclusions increases, and the surface properties deteriorate. Therefore, the Al content is preferably 0.005% to 0.100%. The Al content is more preferably 0.010% or more, and more preferably 0.080% or less. In addition, the Al content is further preferably 0.015% or more, and further preferably 0.070% or less.

[0107] N: 0.0100% or less

[0108] N is an element that has the effect of reducing ductility and toughness by firmly fixing dislocation movement. In the present invention, it is desired to reduce N as an impurity as much as possible, but the N content can be allowed to be up to 0.0100%. Therefore, the N content is preferably less than 0.0100%. The N content is more preferably less than 0.0080%. It should be noted that the lower limit of N is not particularly specified (usually greater than 0%), but excessive reduction will lead to an increase in smelting costs, so N is preferably more than 0.0010%.

[0109] The above-mentioned base material composition may also include, by mass%, selected from

[0110] Nb: (greater than 0%) 0.100% or less,

[0111] V: (greater than 0%) 0.100% or less,

[0112] Ti: (greater than 0%) 0.150% or less,

[0113] Cr: (greater than 0%) less than 1.00%,

[0114] Mo: (greater than 0%) 1.00% or less,

[0115] Cu: (greater than 0%) 1.00% or less,

[0116] Ni: (greater than 0%) less than 1.00%,

[0117] Ca: (greater than 0%) 0.0100% or less,

[0118] B: (greater than 0%) less than 0.0100%

[0119] 1 or more of the following.

[0120] Nb: 0.100% or less

[0121] Nb contributes to the improvement of the strength of steel by forming fine carbides and nitrides in steel. In addition, Nb is an element that contributes to the refinement of the structure by suppressing the coarsening of austenite during hot rolling. In order to obtain the above-mentioned effect, the Nb content is preferably 0.001% or more. On the other hand, if the Nb content is greater than 0.100%, the strength increases excessively and the SSC resistance decreases. Therefore, the Nb content is preferably 0.100% or less. The Nb content is more preferably 0.002% or more, and further preferably 0.005% or more. In addition, the Nb content is more preferably 0.090% or less, and further preferably 0.080% or less.

[0122] Ti: 0.150% or less

[0123] Ti is an element that contributes to improving the strength of steel by forming fine carbides and nitrides in steel. In addition, since Ti has a high affinity with N, it makes N in steel harmless as nitrides, and is an element that contributes to improving the ductility of steel. In order to obtain the above-mentioned effect, the Ti content is preferably 0.001% or more. On the other hand, if the Ti content is greater than 0.150%, the strength increases excessively and the SSC resistance decreases. Therefore, the Ti content is preferably 0.150% or less. The Ti content is more preferably 0.002% or more, and further preferably 0.005% or more. In addition, the Ti content is more preferably 0.140% or less, and further preferably 0.130% or less.

[0124] V: 0.100% or less

[0125] V is an element that contributes to the improvement of the strength of steel by forming fine carbides and nitrides in steel. In order to obtain the above-mentioned effect, the V content is preferably 0.001% or more. On the other hand, if the V content is greater than 0.100%, the strength increases excessively and the SSC resistance decreases. Therefore, the V content is preferably 0.100% or less. The V content is more preferably 0.002% or more, and further preferably 0.005% or more. In addition, the V content is more preferably 0.090% or less, and further preferably 0.080% or less.

[0126] Cr: 1.00% or less

[0127] Cr is an element that improves the hardenability of steel and increases the strength of steel. In order to obtain the above-mentioned effect, the Cr content is preferably 0.01% or more. On the other hand, if the Cr content is greater than 1.00%, hard pearlite, martensite, and austenite are excessively generated, and SSC resistance is reduced. Therefore, the Cr content is preferably 1.00% or less. The Cr content is more preferably 0.02% or more, and further preferably 0.05% or more. In addition, the Cr content is more preferably 0.80% or less, and further preferably 0.60% or less.

[0128] Mo: 1.00% or less

[0129] Mo is an element that improves the hardenability of steel and increases the strength of steel. In order to obtain the above-mentioned effect, the content of Mo is preferably 0.01% or more. On the other hand, if the Mo content is greater than 1.00%, hard pearlite, martensite, and austenite are excessively generated and the SSC resistance is reduced. Therefore, the Mo content is preferably 1.00% or less. The Mo content is more preferably 0.02% or more, and further preferably 0.05% or more. In addition, the Mo content is more preferably 0.80% or less, and further preferably 0.60% or less.

[0130] Cu: 1.00% or less

[0131] Cu is an element that increases the strength of steel by solid solution strengthening. In order to obtain the above-mentioned effect, the Cu content is preferably 0.01% or more. On the other hand, if the Cu content is greater than 1.00%, hard pearlite, martensite, and austenite are excessively generated and SSC resistance is reduced. Therefore, the Cu content is preferably 1.00% or less. The Cu content is more preferably 0.02% or more, and further preferably 0.05% or more. In addition, the Cu content is more preferably 0.80% or less, and further preferably 0.60% or less.

[0132] Ni: 1.00% or less

[0133] Ni is an element that increases the strength of steel by solid solution strengthening. In order to obtain the above-mentioned effect, the Ni content is preferably 0.01% or more. On the other hand, if the Ni content is greater than 1.00%, hard pearlite, martensite, and austenite are excessively generated and SSC resistance is reduced. Therefore, the Ni content is preferably 1.00% or less. The Ni content is more preferably 0.02% or more, and further preferably 0.05% or more. In addition, the Ni content is more preferably 0.80% or less, and further preferably 0.60% or less.

[0134] Ca: 0.0100% or less

[0135] Ca is an element that contributes to the improvement of the ductility of steel by spheroidizing sulfides such as MnS that are thinly stretched in the hot rolling process. In order to obtain the above-mentioned effect, the Ca content is preferably 0.0002% or more. On the other hand, if the Ca content is greater than 0.0100%, Ca oxide clusters are formed in the steel, and the ductility decreases. Therefore, the Ca content is preferably 0.0100% or less. The Ca content is more preferably 0.0005% or more, and further preferably 0.0010% or more. In addition, the Ca content is more preferably 0.0080% or less, and further preferably 0.0060% or less.

[0136] B: 0.0100% or less

[0137] B is an element that improves the hardenability of steel and increases the strength of steel. In order to obtain the above-mentioned effect, it is preferred to contain 0.0001% or more of B. On the other hand, if the B content is greater than 0.0100%, hard pearlite, martensite, and austenite are excessively generated and SSC resistance is reduced. Therefore, the B content is preferably 0.0100% or less. The B content is more preferably 0.0005% or more, and further preferably 0.0008% or more. In addition, the B content is more preferably 0.0080% or less, further preferably 0.0060% or less, and most preferably 0.0040% or less.

[0138] In the above composition, the remainder is Fe and inevitable impurities. Examples of the inevitable impurities of the remainder include Sn, As, Sb, Bi, Co, Pb, Zn, and O. However, within the range that does not hinder the effect of the present invention, it is not prohibited to contain less than 0.1% of Sn, less than 0.05% of As, Sb, and Co, respectively, and less than 0.005% of Bi, Pb, Zn, and O, respectively.

[0139] Next, one embodiment of the method for producing an electric resistance welded steel pipe according to the present invention will be described.

[0140] The hot rolled steel sheet that becomes the billet of the electric resistance welded steel pipe of the present invention is obtained by, for example, heating the billet having the above-mentioned composition to a heating temperature of 1100°C to 1300°C, performing hot rolling at a finishing temperature of 750°C to 850°C (hot rolling process), and then performing cooling at an average cooling rate of 10°C / s to 60°C / s at the center of the plate thickness, a cooling stop temperature of 450°C to 650°C at the center of the plate thickness, and a cooling stop temperature of 250°C to 500°C at the plate surface (cooling process) to obtain a hot rolled steel sheet. Then, the hot rolled steel sheet can be wound with a coil.

[0141] The electric resistance welded steel pipe of the present invention is manufactured by forming the hot rolled steel plate into a cylindrical shape by cold rolling rolls, butting both circumferential ends of the cylindrical shape and performing electric resistance welding (pipe making process), then forming the steel pipe into an electric resistance welded steel pipe material by sizing rolls satisfying the following formula (1) (sizing process), and then applying an internal pressure p (MPa) satisfying the following formula (2) to the inner surface of the electric resistance welded steel pipe material (internal pressure applying process).

[0142] Diameter of sizing roller (mm) ≥ thickness of hot-rolled steel plate (mm) / 0.020···(1)

[0143] X<p≤X×1.5···(2)

[0144] It should be noted that X = (wall thickness of electric resistance welded steel pipe blank (mm) / radius of electric resistance welded steel pipe blank (mm)) × yield strength of electric resistance welded steel pipe material (MPa)

[0145] It should be noted that the above-mentioned cylindrical shape refers to a shape in which the tube circumferential cross section is "C".

[0146] The load of the above-mentioned internal pressure can be implemented by, for example, sealing the pipe end and loading the water pressure inside the pipe with a seal of a rubber material. In addition, in order to stabilize the shape, a mold of a desired diameter can also be used as an outer frame as required.

[0147] In the following description of the manufacturing method, unless otherwise specified, "°C" related to temperature refers to the surface temperature of the steel billet, steel plate and hot-rolled steel plate (hereinafter referred to as "steel plate, etc."). The surface temperature of the steel plate, etc. can be measured using a radiation thermometer, etc. In addition, the temperature at the center of the plate thickness of the steel plate, etc. can be calculated by heat transfer analysis to calculate the temperature distribution in the cross section of the steel plate, etc., and can be obtained by correcting the result by the surface temperature of the steel plate, etc.

[0148] Furthermore, a method for producing a hot-rolled steel plate that is to be a base material of the electric-resistance-welded steel pipe of the present invention will be described in detail.

[0149] In the present invention, the smelting method of the steel billet (steel billet) is not particularly limited. For example, any known smelting method such as a converter, an electric furnace, a vacuum melting furnace, etc. is suitable. The casting method is also not particularly limited. For example, a steel billet of a desired size is manufactured by a known casting method such as a continuous casting method. It should be noted that there is no problem even if agglomeration-block rolling method is applied instead of continuous casting method. For molten steel, secondary refining such as ladle refining can also be performed.

[0150] Heating temperature: 1100℃~1300℃

[0151] When the heating temperature of the steel billet is less than 1100°C, the deformation resistance of the rolled material becomes large and it is difficult to roll. On the other hand, if the heating temperature is greater than 1300°C, the austenite grains become coarse, and it is difficult to obtain fine austenite grains in the subsequent rolling (rough rolling, finish rolling), and it is difficult to ensure the average crystal grain size required by the present invention. Therefore, the heating temperature of the hot rolling process is 1100°C to 1300°C. The heating temperature is more preferably 1120°C or more, and more preferably 1280°C or less.

[0152] It should be noted that in the present invention, in addition to the existing method of temporarily cooling the steel billet (slab) to room temperature and then reheating it after manufacturing, energy-saving direct rolling processes such as loading it into a heating furnace while maintaining the warm sheet state without cooling it to room temperature or rolling it immediately after a small amount of heat preservation can also be applied without problems.

[0153] Finishing rolling end temperature: 750℃~850℃

[0154] In the hot rolling process, when the finishing temperature is less than 750°C, the surface temperature of the steel plate becomes below the ferrite transformation start temperature during the finishing rolling, and a processed ferrite with a high dislocation density is generated, and the SSC resistance is reduced. On the other hand, if the finishing temperature is greater than 850°C, the reduction in the austenite non-recrystallization temperature region is insufficient, and it is difficult to obtain fine austenite grains. As a result, it is difficult to ensure the average crystal grain size required by the present invention. Therefore, the finishing temperature is 750°C to 850°C. The finishing temperature is more preferably 770°C or more, and more preferably 830°C or less.

[0155] In the present invention, the finished plate thickness (plate thickness of the steel plate after finish rolling) is preferably 4 mm or more. On the other hand, the upper limit of the finished plate thickness is not particularly limited, but is preferably 30 mm or less from the viewpoint of temperature management of the steel plate.

[0156] Average cooling rate at the center of plate thickness: 10℃ / s~60℃ / s

[0157] In the cooling process, if the average cooling rate at the center of the plate thickness is less than 10°C / s, the nucleation frequency of ferrite and bainite is reduced, and they will coarsen, so it is difficult to obtain a steel structure with the average crystal grain size required by the present invention, and the strength is reduced. On the other hand, if the average cooling rate is greater than 60°C / s, a large amount of hard structure is generated on the surface of the steel plate, and it is difficult to obtain a steel structure with the structure fraction required by the present invention, and the SSC resistance is reduced. The average cooling rate at the center of the plate thickness is preferably 15°C / s or more, preferably 55°C / s or less.

[0158] In addition, in the present invention, if ferrite is generated before the cooling step, it will coarsen and it will be difficult to obtain a steel structure having an average crystal grain size required by the present invention, and the strength will decrease. Therefore, it is preferred to start the cooling step immediately after the finish rolling is completed.

[0159] Cooling stop temperature at the center of plate thickness: 450℃~650℃

[0160] In the cooling process, if the cooling stop temperature at the center of the plate thickness is less than 450°C, the cooling stop temperature at the surface of the steel plate becomes too low, a large amount of hard structure is generated on the surface of the steel plate, it is difficult to obtain a steel structure with the structure fraction required by the present invention, and the SSC resistance is reduced. On the other hand, if the above-mentioned cooling stop temperature is greater than 650°C, the nucleation frequency of ferrite or bainite is reduced, they will coarsen and it will be difficult to obtain a structure with the average crystal grain size required by the present invention, and the strength is reduced. The cooling stop temperature at the center of the plate thickness is preferably above 480°C and preferably below 620°C.

[0161] Cooling stop temperature of plate surface: 250℃~500℃

[0162] In the cooling process, if the cooling stop temperature of the plate surface is less than 250°C, a large amount of hard structure is generated on the surface of the steel plate, and it is difficult to obtain a steel structure with the structure fraction required by the present invention, and the SSC resistance is reduced. On the other hand, if the above-mentioned cooling stop temperature is greater than 500°C, the cooling stop temperature in the center of the plate thickness becomes too high, and the nucleation frequency of ferrite or bainite in the center of the plate thickness decreases, and they will coarsen, so it is difficult to obtain a structure with the average crystal grain size required by the present invention, and the strength is reduced. The cooling stop temperature of the plate surface is preferably 280°C or more, preferably 470°C or less.

[0163] In the present invention, unless otherwise specified, the average cooling rate is a value (cooling rate) obtained by ((plate thickness center temperature of steel plate before cooling - plate thickness center temperature of hot-rolled steel plate after cooling) / cooling time).

[0164] In addition, the cooling method includes water cooling such as spraying water from a nozzle and cooling by spraying a cooling gas, etc. In the present invention, it is preferable to cool both surfaces of the steel plate under the same conditions and perform cooling operation (treatment) on both surfaces of the steel plate.

[0165] After the cooling process, the hot-rolled steel sheet is formed into a cylindrical shape by cold rolling rollers, and the two circumferential ends of the cylinder are butted and resistance welded (pipe making process). Next, the resistance welded steel tube billet is made by sizing rollers (sizing process). In the sizing process, bending deformation occurs in the tube axis direction along the roller shape when passing through the rollers, and residual stress is generated in the tube axis direction. The greater the bending strain of the above bending deformation, the greater the absolute value of the residual stress in the tube axis direction becomes. The smaller the diameter of the sizing roller and the thicker the plate thickness of the hot-rolled steel sheet, the greater the above bending strain becomes.

[0166] Therefore, in the present invention, from the viewpoint of reducing the shear residual stress, the diameter of the sizing roll is set to satisfy the above formula (1) in order to reduce the absolute value of the residual stress in the tube axis direction.

[0167] When the diameter of the sizing roll is smaller than the right side of the above formula (1), it is difficult to obtain the shear residual stress required by the present invention. It should be noted that the upper limit of the diameter of the sizing roll is not particularly specified, but if the sizing roll becomes larger, the load on the equipment increases, so the diameter of the sizing roll is preferably 2000 mm or less.

[0168] In the internal pressure loading step after the sizing step, the electric resistance welded steel tube material is expanded to generate tensile stress in the tube circumferential direction, thereby reducing the absolute value of the residual stress in the tube circumferential direction.

[0169] The greater the internal pressure p (MPa) in the internal pressure loading step, the smaller the absolute value of the residual stress in the pipe circumferential direction. The greater the radius of the steel pipe and the smaller the wall thickness of the steel pipe, the higher the tensile stress generated in the pipe circumferential direction.

[0170] The left side (X) of the above formula (2) corresponds to the internal pressure p when the tensile stress generated in the pipe circumferential direction becomes equal to the yield stress of the electric resistance welded steel pipe material.

[0171] In the present invention, from the viewpoint of reducing the shear residual stress, in order to reduce the absolute value of the residual stress in the pipe axial direction, the internal pressure p is set to a value greater than the left side (X) of the formula (2), and the electric resistance welded steel pipe billet is expanded to the plastic region. On the other hand, if the internal pressure p becomes a value greater than the right side (X×1.5) of the formula (2), the absolute value of the residual stress in the pipe circumferential direction becomes smaller, but the amount of work hardening due to pipe expansion becomes too large, the dislocation density on the pipe surface increases, and the SSC resistance decreases.

[0172] The high-strength electric-resistance welded steel pipe of the present invention is manufactured by the manufacturing method described above. The high-strength electric-resistance welded steel pipe of the present invention exhibits excellent SSC resistance and also has high yield strength.

[0173] Example

[0174] Hereinafter, the present invention will be described in further detail based on examples. It should be noted that the present invention is not limited to the following examples.

[0175] Molten steel having the chemical composition shown in Table 1 was melted to obtain slabs (steel slabs). The obtained slabs were hot-rolled and cooled under the conditions shown in Table 2 to obtain hot-rolled steel sheets having the finished sheet thickness (mm) shown in Table 2.

[0176] The hot rolled steel sheet was formed into a cylindrical open pipe (round steel pipe) by cold rolling, the butt joint of the open pipe was subjected to electric resistance welding (pipe making process), and the diameter was reduced by rollers arranged vertically and horizontally (sizing process), thereby obtaining an electric resistance welded steel pipe billet having a radius (mm) and a wall thickness (mm) shown in Table 2 and a length of 12 m.

[0177] Both ends of the electric resistance welded steel pipe material were sealed with rubber seals, and a water pressure p (MPa) was applied to the inner surface of the pipe (internal pressure loading step) to prepare an electric resistance welded steel pipe.

[0178]

[0179]

[0180] Various test pieces were collected from the electric resistance welded steel pipe thus obtained, and the average crystal grain size measurement, structure observation, tensile test, residual stress measurement, and four-point bending corrosion test were carried out by the following methods. Here, for various test pieces other than the residual stress measurement, the electric resistance welded portion was set to 0°, and the base material portion separated from the electric resistance welded portion by 90° in the pipe circumferential direction was collected.

[0181] [Measurement of average crystal particle size]

[0182] The test piece for measurement is collected from the electric resistance welded steel pipe so that the measurement surface becomes a cross section parallel to both the tube axis direction and the wall thickness direction, and is mirror-polished and produced. The average crystal grain size is measured using the SEM / EBSD method. Regarding the crystal grain size, the azimuth difference between adjacent grains is determined, and the boundary with an azimuth difference of 15° or more is measured as the grain boundary. The arithmetic mean of the crystal grain size (equivalent to the diameter of a circle) is obtained from the obtained grain boundary as the average crystal grain size. As measurement conditions, the acceleration voltage is 15 kV, the measurement area is 200 μm × 200 μm, the measurement step length (measurement resolution) is 0.5 μm, and the measurement values ​​of 5 fields of view are averaged. It should be noted that in the crystal grain size analysis, crystals with a crystal grain size of less than 2.0 μm are removed from the analysis object as measurement noise.

[0183] In addition, the measurement position is the center of the wall thickness, and the histogram of the crystal grain size distribution at each position is calculated (a graph with the horizontal axis as the crystal grain size and the vertical axis as the existence ratio of each crystal grain), and the average crystal grain size is obtained as the arithmetic average of the crystal grain size.

[0184] 〔Organization Observation〕

[0185] The test piece for organization observation was collected from the electric resistance welded steel pipe in such a way that the observation surface became a cross section parallel to both the pipe axis direction and the wall thickness direction, mirror polished, and then etched with nitric acid ethanol solution (nital). For organization observation, an optical microscope (magnification: 1000 times) or a scanning electron microscope (SEM, magnification: 1000 times) was used to observe and photograph the organization at the center of the wall thickness and at a position of 0.1 mm from the inner surface of the pipe to the outside in the radial direction of the pipe. The area ratios of ferrite, bainite, and the rest (pearlite, martensite, austenite) were calculated from the obtained optical microscope image and SEM image. The area ratio of each organization was observed in 5 viewing fields and calculated as the average value of the values ​​obtained in each viewing field. Here, the area ratio obtained by organization observation is taken as the volume ratio of each organization.

[0186] Here, ferrite refers to a product resulting from diffusion transformation, and has a low dislocation density and a substantially recovered structure, including polygonal ferrite and quasi-polygonal ferrite.

[0187] Bainite is a duplex structure of lath-shaped ferrite and cementite with high dislocation density.

[0188] Pearlite is a eutectic structure of iron and iron-carbon compounds (ferrite + cementite), showing a layered structure in which linear ferrite and cementite are arranged alternately. In addition, it includes degenerate pearlite, which is a structure in which point-like cementite is regularly arranged in ferrite.

[0189] Martensite is a lath-shaped low-temperature transformation structure with a very high dislocation density. In SEM images, it shows a bright contrast compared to ferrite and bainite.

[0190] It should be noted that it is difficult to distinguish martensite and austenite in optical microscope images and SEM images. Therefore, the area ratio of the structure observed as martensite or austenite in the obtained SEM image is measured, and then the value obtained by subtracting the volume ratio of austenite measured by the method described later is used as the volume ratio of martensite.

[0191] The volume fraction of austenite is measured by X-ray diffraction. For the test piece for measuring the center of the wall thickness, the diffraction surface is ground to the center of the wall thickness, and then the surface processing layer is removed by chemical polishing. In addition, for the test piece for measuring at the 0.1 mm position, the diffraction surface is mirror-polished to the position 0.1 mm outside the tube in the radial direction from the inner surface of the tube, and then the ground surface is chemically polished to remove the surface processing layer. The Kα line of Mo is used for measurement, and the integrated intensity of the (200), (220), and (311) planes of fcc iron and the (200) and (211) planes of bcc iron are respectively calculated. The volume fraction of austenite is calculated by calculating the ratio of the standardized integrated intensity of austenite in a manner that the standardized integrated intensity obtained by dividing each value by the theoretical intensity value is proportional to the volume fraction of each phase.

[0192] 〔Tensile test〕

[0193] Regarding the test pieces, JIS No. 5 tensile test pieces were collected from the base material of the electric resistance welded steel pipe and the base material of the electric resistance welded steel pipe so that the tensile direction became parallel to the pipe axis direction. The tensile test was carried out in accordance with the provisions of JIS Z 2241. However, the yield strength (MPa) is the flow stress at a nominal strain of 0.5%.

[0194] 〔Residual stress measurement〕

[0195] The absolute value of the shear residual stress on the inner surface of the tube was measured by X-ray diffraction on the surface of the inner surface of the electric resistance welded steel tube in the center of the longitudinal direction, which was electrolytically polished to 100 μm. The X-ray source was CrKα line, the tube voltage was 30 kV, and the tube current was 1.0 mA. The measurement was performed by the cosα method, and the measured lattice plane was (211). It should be noted that in this measurement, the residual stress in the tube axis direction and the tube circumferential direction was measured in the inner surface of the tube at each position (12 places) at 30 degrees intervals in the tube circumferential direction of the resistance welded part and based on it, and the absolute value of the shear residual stress was obtained as the absolute value of ((residual stress in the tube axis direction (MPa) - residual stress in the tube circumferential direction (MPa)) / 2).

[0196] However, the residual stress in the tube axis direction or the tube circumferential direction is positive in the case of tension and negative in the case of compression, and when there is no residual stress in the tube axis direction or the tube circumferential direction, the value is set to 0. The absolute value of the shear residual stress is obtained at each position, and the maximum value thereof is taken as the absolute value of the shear residual stress of the present invention.

[0197] In addition, the residual stress in the pipe axial direction and the residual stress in the pipe circumferential direction in Table 3 are values ​​when the absolute values ​​of the shear residual stress are respectively the maximum.

[0198] Furthermore, the absolute values ​​of the residual stresses in the pipe circumferential direction at each position were obtained, and it was confirmed whether the minimum value thereof was 10 MPa or more.

[0199] 〔Four-point bending corrosion test〕

[0200] A 5 mm high×15 mm wide×115 mm long four-point bending corrosion test piece was collected from the electric resistance welded steel pipe so that the width direction of the corrosion test piece was parallel to the pipe circumferential direction of the electric resistance welded steel pipe and the length direction of the corrosion test piece was parallel to the pipe axial direction of the electric resistance welded steel pipe.

[0201] Regarding the outer side of the bend, i.e. the corrosion surface, the surface state is kept intact and collected. According to the EFC16 specification, a tensile stress of 90% of the yield strength of the electric resistance welded steel pipe obtained by the above-mentioned tensile test is loaded on the corrosion surface of the collected test piece, and a 4-point bending corrosion test is carried out at a hydrogen sulfide partial pressure of 1 bar using the NACE specification TM0177 Solution A solution. After the test piece is immersed in the above solution for 720 hours, it is confirmed whether cracking occurs. In addition, at the 1 / 3 position and the 2 / 3 position in the width direction of the test piece after the test, an observation test piece is collected so that the observation surface becomes a cross-section parallel to the thickness direction and the length direction.

[0202] The obtained observation test piece was mirror-polished and observed using an optical microscope, and the depth and width of all pitting corrosion generated in the portion subjected to tensile stress were measured to determine the maximum pitting corrosion depth and the maximum value of the pitting corrosion (depth / width) ratio.

[0203] The obtained results are shown in Table 3.

[0204]

[0205] In Table 3, No. 1 to 6 are examples of the present invention, and No. 7 to 13 are comparative examples.

[0206] In the electric resistance welded steel pipe of the present invention example, in the steel structure at the center of the wall thickness of any base material portion, the total volume fraction of ferrite and bainite is 90% or more, the average crystal grain size is 9.0 μm or less, in the steel structure at a position of 0.1 mm from the inner surface of the pipe toward the outer side in the radial direction of the pipe, the total volume fraction of ferrite and bainite is 95% or more, the absolute value of the residual stress in the circumferential direction of the inner surface of the pipe is 10 MPa or more, and the absolute value of the shear residual stress on the inner surface of the pipe is 300 MPa or less.

[0207] Furthermore, the electric resistance welded steel pipes of these inventive examples had a yield strength of 400 MPa or more in the base material portion in any tensile test, did not crack in the four-point bending corrosion test, had a pitting depth of less than 250 μm, and had a maximum value of (depth / width) of less than 3.0.

[0208] On the other hand, in the electric resistance welded steel pipe of Comparative Example No. 7, since the cooling stop temperature at the center of the plate thickness in the cooling process is low, the cooling stop temperature at the plate surface becomes low, a large amount of hard structure is generated in the center of the wall thickness and at the 0.1 mm position, and the total volume fraction of ferrite and bainite is lower than the range of the present invention, resulting in difficulty in obtaining the desired SSC resistance.

[0209] In the electric resistance welded steel pipe of Comparative Example No. 8, the cooling stop temperature at the center of the plate thickness in the cooling process was high, so the cooling stop temperature at the plate surface became high, and the average grain size at the center of the wall thickness exceeded the range of the present invention, resulting in difficulty in obtaining the desired yield strength.

[0210] In the electric resistance welded steel pipe No. 9 of the comparative example, since the average cooling rate at the center of the plate thickness in the cooling step was too fast, a large amount of hard structure was generated at the 0.1 mm position, and the total volume fraction of ferrite and bainite was lower than the range of the present invention, resulting in that the desired SSC resistance could not be obtained.

[0211] Regarding the electric resistance welded steel pipe No. 10 of Comparative Example, the average cooling rate at the center of the plate thickness in the cooling process was too slow, the cooling stop temperature at the plate surface deviated from the upper limit, and the average crystal grain size at the center of the wall thickness exceeded the range of the present invention, resulting in the failure to obtain the desired yield strength.

[0212] In the electric resistance welded steel pipe No. 11 of the comparative example, since the diameter of the sizing roll used in the sizing step is below the range of formula (1), the absolute value of the shear residual stress on the inner surface of the pipe exceeds the range of the present invention, and as a result, the desired SSC resistance cannot be obtained.

[0213] In the electric resistance welded steel pipe No. 12 of the comparative example, since the internal pressure p in the internal pressure loading step is lower than the range of formula (2), the absolute value of the shear residual stress on the inner surface of the pipe exceeds the range of the present invention, and as a result, the desired SSC resistance cannot be obtained.

[0214] In the electric resistance welded steel pipe of Comparative Example No. 13, since the internal pressure p in the internal pressure loading step exceeds the range of formula (2), the absolute value of the circumferential residual stress on the inner surface of the pipe is below the range of the present invention, resulting in failure to obtain the desired SSC resistance.

Claims

1. A resistance welded steel pipe having a base metal portion and a resistance welded portion, The absolute value of the residual stress in the circumferential direction of the inner surface of the electric resistance welded steel pipe is 10 MPa or more. The absolute value of the shear residual stress on the inner surface of the tube is less than 300 MPa, The total volume fraction of ferrite and bainite in the steel structure at the center of the wall thickness of the base material portion is 90% or more, and the average grain size at the center of the wall thickness is 9.0 μm or less. The total volume fraction of ferrite and bainite in the steel structure at a position 0.1 mm outward in the radial direction of the tube from the inner surface of the tube of the base material portion is 95% or more.

2. The electric resistance welded steel pipe according to claim 1, characterized in that: The component composition of the base material portion includes, by mass %, C:0.020%~0.150%, Si: 0.01% to 0.50%, Mn: 0.30% to 2.00%, P: 0.050% or less, S: 0.0200% or less, Al:0.005%~0.100%, N: 0.0100% or less, The remainder is Fe and inevitable impurities.

3. The electric resistance welded steel pipe according to claim 2, characterized in that: The composition of the ingredients, in terms of mass %, also includes Nb: 0.100% or less, V: 0.100% or less, Ti: 0.150% or less, Cr: 1.00% or less, Mo: 1.00% or less, Cu: 1.00% or less, Ni: 1.00% or less, Ca: 0.0100% or less, B: 0.0100% or less 1 or 2 or more of the above.

4. A method for manufacturing an electric resistance welded steel pipe, the method for manufacturing an electric resistance welded steel pipe according to any one of claims 1 to 3, characterized in that: include: In the hot rolling process, the steel billet is heated to a heating temperature of 1100°C to 1300°C, and then hot rolled at a finishing temperature of 750°C to 850°C. A cooling process, after the hot rolling process, is performed at an average cooling rate of 10°C / s to 60°C / s at the center of the plate thickness, a cooling stop temperature of 450°C to 650°C at the center of the plate thickness, and a cooling stop temperature of 250°C to 500°C on the plate surface to produce a hot rolled steel plate; a pipe making step, after the cooling step, forming the hot-rolled steel sheet into a cylindrical shape by cold rolling rolls, butting both circumferential ends of the cylindrical shape and performing resistance welding; A sizing step, after the tube making step, the steel tube billet is made into an electric resistance welded steel tube billet by a sizing roller satisfying the following formula (1); as well as An internal pressure loading step, after the sizing step, loading an internal pressure p (MPa) satisfying the following formula (2) on the inner surface of the electric resistance welded steel pipe billet to produce an electric resistance welded steel pipe; Diameter of sizing roller (mm) ≥ thickness of hot-rolled steel plate (mm) / 0.020···(1) X<p≤X×1.5···(2) In addition, X=(wall thickness of electric resistance welded steel pipe material (mm) / radius of electric resistance welded steel pipe material (mm))×yield strength of electric resistance welded steel pipe material (MPa).

Citation Information

Patent Citations

  • Electroseamed steel pipe for linepipe and manufacturing method therefor

    JP2017179482A